Is the world becoming spherical - "Gupta, Anil Kumar" (Noida, 2009)
This book explains in layman's language what's happening in India and World Economies around us. The integration and globalization achieved over the past few decades making the world 'flat' look to be turning 'spherical' again as edges, peaks and troughs have started showing.
Keywords: English-Fiction